2017
DOI: 10.1016/j.margeo.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Elemental and mineralogical analysis of marine and coastal sediments from Phra Thong Island, Thailand: Insights into the provenance of coastal hazard deposits

Abstract: Sediment records left by coastal hazards (e.g. tsunami and/or storms) may shed light on the sedimentary and hydrodynamic processes happening during such events. Modern onshore and offshore sediment samples were compared with the 2004 Indian Ocean Tsunami, three palaeotsunami and a 2007 storm deposit from Phra Thong Island, Thailand, to determine provenance relationships between these coastal overwash deposits. Sedimentological and stratigraphic characteristics are generally inadequate to discriminate tsunami a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 52 publications
(95 reference statements)
1
26
0
1
Order By: Relevance
“…This implies that storms can deposit sediment on Phra Thong Island, but from this solitary example, fan development may be restricted to a few 10 s of metres from the modern shoreline – unlike the kilometre-scale inundation and sedimentation caused by the 2004 IOT. The granulometric properties of the sediments collected from the washover fans are statistically indistinguishable from the modern-day beachface sediments and are geochemically similar to Sandsheets A and C, nearshore and beachface deposits suggesting a local and similar source of sediments supplying Sandsheets A and C and the storm deposit35.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…This implies that storms can deposit sediment on Phra Thong Island, but from this solitary example, fan development may be restricted to a few 10 s of metres from the modern shoreline – unlike the kilometre-scale inundation and sedimentation caused by the 2004 IOT. The granulometric properties of the sediments collected from the washover fans are statistically indistinguishable from the modern-day beachface sediments and are geochemically similar to Sandsheets A and C, nearshore and beachface deposits suggesting a local and similar source of sediments supplying Sandsheets A and C and the storm deposit35.…”
mentioning
confidence: 87%
“…The 2004 IOT sediments have a bimodal sediment distribution that is dominated by quartz (85 to 95%), benthic foraminifera and shell fragments (8 to 15%), muscovite (4%), heavy minerals (1.7 to 3%) and a low organic content (1.5 to 2.5%)3032. The <0.125 mm component as determined by X-ray diffraction (XRD) is dominated by quartz (52 to 57%), but feldspars (orthoclase and microcline), aragonite, zircon, muscovite, monazite, kaolinite, cassiterite and labradorite are present, attesting to the nearshore marine sediment source35.…”
mentioning
confidence: 99%
“…The utility of proxy data in interpreting overwash (i.e. tsunami and storm inundation) deposits can be strengthened by constraining their spatial distribution in the modern environment (Pilarczyk et al, 2011;Pham et al, 2017;Kosciuch et al, 2018). Such baseline studies provide a basis that anomalous sand layers, contained within the geological record, can be interpreted.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to obtain information on where sediment has eroded and deposited and whether topographic changes caused by the local sediment runoff or deposition are the results of action from inflow or backwash (e.g. Pham et al 2018). This information determines the sediment budget in the system before and after the tsunami and is therefore important for considering topographic recovery.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, numerical simulation results suggest that there is little transportation of sediments from the shoreline by the first inflowing wave and that inland deposits were formed by sediment transported from the sea. Similarly, analysis of microfossils(Sawai et al, 2009) from preserved 2004 IOT tsunami deposits inland suggests that tsunami deposits on Phra Thong Island originated from shallow nearshore zone Pham et al (2018). suggested that sediment grain sizes and mineralogy were most similar to those of nearshore sediments, but that geochemically the 2004 IOT sediments were a combination of nearshore and onshore sources, but that quantifying the contributions from different environments remains a challenge.…”
mentioning
confidence: 99%